ANALISIS KOMUNIKASI PEMASARAN TERPADU DALAM MENINGKATKAN MINAT CALON PESERTA DIDIK SMA CENDANA PEKANBARU - Natya Wulandari; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Pekanbaru has 43 private schools, one of them is Cendana Senior High School Pekanbaru which is in PT. Chevron Pacific Indonesia area. It starts as part pf an education facility for children od Chevron employess. Howeve, in 2005 this school opens for the public and has potential that’s need to know for children school, it’s one of the well-known schools in has given by IHRDP around 2017. Has a lot private school in Pekanbaru make Cendana Senior High School needs to compete and egage in integrated marketing communication use promotion to get the maximal result, such as interactive marketing, personal selling, event and advertising and using SWOT analysis to look the strategic marketing in Cendana Senior High School Pekanbaru. This research use qualitative research methods with descriptive analysis, ehich is illustrated by the subject or object base on fact. The totl of informants interviewed was 5, which is taken by purposive technique. Data collected through interview,observation, and documentation. The data analysis technique use a interactive, analysis mode; by four stage, such as collecting data, data reduction, organizing of data, and conclusion. The verification data technique by triangulation.The result of the research is Cendanan Senior High School in integrated marketing communication activity, or IMC uses promotion, like interactive marketing by facebook, instagram, youtube, and website. The personal selling activity is done with promotions in Junior High School as target and makes a talent performance in Mall and CFD. The annual event holds tryout UNBK and Cendana Sport Music Festival by present other student in Junior as participant. Last, advertising activity by promoting in television, newspaper, radio and banners. All IMC events are considered maximally with many factors, evalution and analysis, so the strategy of marketing communication media will be proper and better.